KESADARAN TENTANG KANKER SERVIKS DAN UPAYA PENCEGAHANNYA PADA KARYAWATI UNIVERSITAS SURABAYA - Herlyn Diana Bulu (CALYPTRA, 2014)
The Death of cervical cancer still ranks first female cancer in developing countries, including Indonesia. University of Surabaya female employees as well as every woman have a risk for cervical cancer. Cervical cancer can be prevented by vaccination and Pap smear. This research on cervical cancer awareness and its prevention bad done at the University of Surabaya employee. The design of this study is a cross sectional survey with purposive sampling method which had been conducted on the female employee (n = 111) from May to June 2013. The research instrument used was a questionnaire which was divided into two aspects: awareness and prevention of the disease. The results showed 57.66% of respondents had a high awareness and 14.14% of respondents had done vaccination and Pap smear to prevent cervical cancer. There is a significant difference in the level of awareness between the respondents who had been married with the unmarried employees.